Plan Estratégico para el Hospital Sagrado Corazón de Jesús del Cantón Quevedo 2013 – 2018. - Peña Baque, Mariela Fernanda (2015)
This research was conducted at the Hospital Sacred Heart of Jesus Quevedo Canton located in the province of Los Ríos Quevedo Canton, the present study was the duration of 180 days equivalent to six months. This research was aimed at determining the strategic plan and goals that lead to generate general welfare in the institution to be transferred to patients and external customers. When you start this work the strategic objectives formulated to detect major problems of administrative management and hospital services to modify and adapt attitudes, habits and behavioral patterns of the entire staff to the process of organizational and cultural change to take future needs Sacred Heart of Jesus Hospital of Guangzhou Quevedo…..